Urban-rural income disparities and atmospheric contamination: Aggravating or restraining? - Wu, Chuanhao; Zhang, Zhixin; Elahi, Ehsan; Mu, Guoting; Zhao, Peng (Frontiers in Environmental Science, 2022)
This article constructed the local effect and significant interaction model of the urban-rural income disparities with atmospheric contamination and conducted theoretical analysis and empirical tested the urban-rural income disparity influences regional atmospheric contamination. Data were collected from 30 Chinese provinces from 2005 to 2019, and panel regression was employed. The empirical results found that the widening income disparities between urban and rural areas will significantly increase local atmospheric contamination, and there is a significant spatial dependence on regional atmospheric contamination. When the atmospheric contamination in the immediate region is severe, the local atmospheric contamination also worsens. At the same time, the spatial spillover effect of the central area on the surrounding atmospheric contamination is significant and positively affected by the urban-rural income disparities in the central area. Expanding the urban-rural disparities will significantly increase the atmospheric contamination in central and surrounding areas. The regression results were still robust after replacing the core variables and the spatial weight calculation method. Furthermore, results found the income disparities between urban and rural areas to increase agricultural chemicals investment and rural non-agricultural economic output. It significantly and positively influenced atmospheric contamination. The income disparities between urban and rural areas of atmospheric pollution around the region were heterogeneity. The widening income disparities can significantly increase atmospheric contamination levels in less technologically advanced and more polluted areas.